An agile optical layer restoration method for router failures. - Chiu, A.L.
The optical layer can provide its IP clients with rapid and efficient restoration for link failures; however, its inability to protect against router failures erodes its attractiveness. Here, we propose a joint IP/optical restoration mechanism suitable for IP offices with a minimum of two backbone routers and an optical cross-connect. The OXC is used to reterminate OC-48/OC-192 links from a failed backbone router to its mate. The entire interoffice portion of the reterminated link is reused, thus minimizing the amount of additional link capacity required to protect against router failures. A similar approach applicable when there are tunable transceivers but no OXC is also described.
Keywords: IP clients; OC-48/OC-192 links; OXC; Agile optical layer restoration; Backbone routers; Optical cross-connect.; Retermination; Router failures; Tunable transceivers